First description of phosphofructokinase deficiency in spain: identification of a novel homozygous missense mutation in the PFKM gene - Vives Corrons, Joan-Lluis; Koralkova, Pavla; Grau, Josep M.; Mañú Pereira, Maria d.; Van Wijk, Richard (Frontiers in Physiology, 2013)
Phosphofructokinase deficiency is a very rare autosomal recessive disorder, which belongs to group of rare inborn errors of metabolism called glycogen storage disease. Here we report on a new mutation in the phosphofructokinase (PFK) gene PFKM identified in a 65-year-old woman who suffered from lifelong intermittent muscle weakness and painful spasms of random occurrence, episodic dark urines, and slight haemolytic anaemia. After ruling out the most common causes of chronic haemolytic anaemia, the study of a panel of 24 enzyme activities showed a markedly decreased PFK activity in red blood cells from the patient. DNA sequence analysis of the PFKM gene subsequently revealed a novel homozygous mutation: c.926A>G; p.Asp309Gly. This mutation is predicted to severely affect enzyme catalysis thereby accounting for the observed enzyme deficiency. This case represents a prime example of classical PFK deficiency and is the first reported case of this very rare red blood cell disorder in Spain.